Infrastructure sustainability and design - Pollalis, Spiro N., 1954- (New York : Routledge, 2012)
You're overseeing a large-scale project, but you're not an engineering or construction specialist, and so you need an overview of the related sustainability concerns and processes. To introduce you to the main issues, experts from the fields of engineering, planning, public health, environmental design, architecture, and landscape architecture review current sustainable large-scale projects, the roles team members hold, and design approaches, including alternative development and financing structures. They also discuss the challenges and opportunities of sustainability within infrastructural systems, such as those for energy, water, and waste, so that you know what's possible. And best of all, they present here for the first time the Zofnass Environmental Evaluation Methodology guidelines, which will help you and your team improve infrastructure design, engineering, and construction.
Introduction : Sustainability, a broad perspective / Spiro Pollalis and Daniel Schodek -- Climate change and infrastructure / Richard John -- Resource allocation / Gregory Norris -- Infrastructure and nature : reciprocal effects and patterns for our future / Richard T.T. Forman -- Quality of life / Anthony Kane -- Sustainable wellness : the convergence of social and ecological well-being / Alexios Monolpolis -- Water infrastructure and sustainablity / Tom A. Pedersen -- The evolution of urban water and energy infrastructure systems / John Norton Jr. -- Sustainability aspects of large-scale wind power development / George C. Kendrick -- Sustainable solid waste infrastructure / Mike W. McLaughlin and Lisa K. McDaniel -- Sustainable transportation infrastructure / Susannah Kerr Adler [and others] -- Transportation : aviation/airports / James S. Grant et al. -- Sustainability in ports, freight, and logistics / Erin Hyland and Joe Bryan -- Ecological infrastructure / Christopher Benosky and Shaun O'Rourke -- Issues in assessing urban infrastructures / The Zofnass Program Team -- Current environmental evaluation approaches / The Zofnass Program Team -- The Zofnass rating system for infrastructure sustainability and decision making / Andreas Georgoulias and Jill Allen -- Economic assessments of the value of sustainability / John Williams, Stephane Larocque and Lidia Berger -- Sustainable cities : oxymoron or the shape of the future? / Annissa Alusi [and others] -- Intelligent infrastructures / Dimitris Papanikolaou -- Landscape infrastructure : urbanism beyond engineering / Pierre Bélanger -- Shaping the built environment and infrastructure to improve our quality of life / Bill Valentine -- Why ecological urbanism? Why now? / Mohsen Mostafavi.
Includes bibliographical references and index.
Also issued online.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: City planning -- Environmental aspects; Urban ecology (Sociology); Sustainable development; Ecological engineering; Electronic books